2014
DOI: 10.1371/journal.pone.0109010
|View full text |Cite
|
Sign up to set email alerts
|

The Consolidation of Implicit Sequence Memory in Obstructive Sleep Apnea

Abstract: Obstructive Sleep Apnea (OSA) Syndrome is a relatively frequent sleep disorder characterized by disrupted sleep patterns. It is a well-established fact that sleep has beneficial effect on memory consolidation by enhancing neural plasticity. Implicit sequence learning is a prominent component of skill learning. However, the formation and consolidation of this fundamental learning mechanism remains poorly understood in OSA. In the present study we examined the consolidation of different aspects of implicit seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 44 publications
5
27
2
Order By: Relevance
“…Based on this estimation of a nearly zero effect (and similar previous findings showing no change in the offline period, (Csabi et al, 2015;Csabi et al, 2014;Nemeth et al, 2010;Song et al, 2007)), we expected no change in statistical knowledge over the 24-h delay, and consequently, no required sample size was calculated here to detect a significant change. Instead, Bayes factor (BF) was computed on the collected data of the current study to determine whether there is enough evidence to accept the null-hypothesis of no offline change (for more details see the last paragraph of the section Statistical Analysis).…”
Section: Justification Of the Required Sample Sizesupporting
confidence: 73%
See 1 more Smart Citation
“…Based on this estimation of a nearly zero effect (and similar previous findings showing no change in the offline period, (Csabi et al, 2015;Csabi et al, 2014;Nemeth et al, 2010;Song et al, 2007)), we expected no change in statistical knowledge over the 24-h delay, and consequently, no required sample size was calculated here to detect a significant change. Instead, Bayes factor (BF) was computed on the collected data of the current study to determine whether there is enough evidence to accept the null-hypothesis of no offline change (for more details see the last paragraph of the section Statistical Analysis).…”
Section: Justification Of the Required Sample Sizesupporting
confidence: 73%
“…It has widely been shown that implicit learning relies mainly on the fronto-striatal networks (Daw et al, 2005;Doyon et al, 2009;Hikosaka et al, 1999;Poldrack et al, 2005;Reber, 2013). Previous studies have found dissociation between implicit learning/retention and other forms of learning/memory in other clinical populations, showing intact implicit learning/retention and impairments in short-term, working and declarative memory in the same group of patients (e.g., patients with sleep disorders, (Csabi et al, 2015(Csabi et al, , 2014Virag et al, 2015)). Those findings suggest that implicit learning/memory might be less susceptible to illness compared to other forms of learning/memory (Reber, 1993;Reber and Allen, 2000;Reber, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…7 Recently, a number of studies have shown that patients with obstructive sleep apnea (OSA) do not demonstrate these motor skill improvements following a sleep episode. [8][9][10][11] Furthermore, this impairment has been shown to be associated with the extent of sleep fragmentation occurring during intervening sleep. 9 To our knowledge, it is still unknown if this impairment can be alleviated by effective treatment of OSA.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to Borragán et al (2015) we found dissociation in the effect of sleep (and/or sleep disorder) on offline changes of general motor skills and sequence-specific learning: adult OSA patients showed impaired consolidation of general motor but not on sequence-specific learning (Csabi et al, 2014). To our knowledge, the current study is the first to assess the effects of sleep disorder on declarative and non-declarative memory Frontiers in Human Neuroscience | www.frontiersin.orgfunctions before and after a nighttime sleep in children.…”
Section: Introductionsupporting
confidence: 57%
“…Previous studies examined memory encoding and consolidation before and after sleep in patients with sleep apnea in adults, and showed that declarative and some aspects of non-declarative memory performance is affected in patients with OSA Csabi et al, 2014). Similarly to Borragán et al (2015) we found dissociation in the effect of sleep (and/or sleep disorder) on offline changes of general motor skills and sequence-specific learning: adult OSA patients showed impaired consolidation of general motor but not on sequence-specific learning (Csabi et al, 2014).…”
Section: Introductionsupporting
confidence: 55%